1989
DOI: 10.1037/0033-295x.96.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Health complaints, stress, and distress: Exploring the central role of negative affectivity.

Abstract: Most current models in health psychology assume that stress adversely affects physical health. We re-examined this assumption by reviewing extensive data from the literature and from six samples of our own, in which we collected measures of personality, health and fitness, stress, and current emotional functioning. Results indicate that self-report health measures reflect a pervasive mood disposition of negative affectivity (NA); self-report stress scales also contain a substantial NA component. However, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

143
2,101
21
60

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,815 publications
(2,325 citation statements)
references
References 170 publications
(261 reference statements)
143
2,101
21
60
Order By: Relevance
“…It focuses specifically on negative affect without including items relating to somatic complaints or health. It has demonstrated good internal consistency (r = .82, n = 872) (Watson & Pennebaker, 1989).…”
Section: Methodsmentioning
confidence: 97%
“…It focuses specifically on negative affect without including items relating to somatic complaints or health. It has demonstrated good internal consistency (r = .82, n = 872) (Watson & Pennebaker, 1989).…”
Section: Methodsmentioning
confidence: 97%
“…Individuals who report frequent nightmares also report higher levels of neuroticism, a global personality dimension conceptually and empirically related to propensity for negative emotional reactivity (Eysenck & Eysenck, 1975;Watson & Pennebaker, 1989). Three independent investigations (Berquier & Ashton, 1992;Blagrove et al, 2004;Zadra & Donderi, 2000) demonstrated significantly higher levels of neuroticism as measured by the Eysenck Personality Questionnaire (EPQ; Eysenck & Eysenck, 1975) for individuals with frequent nightmares compared with controls.…”
Section: Nightmares Are Associated With Neuroticism and Global Symptomentioning
confidence: 99%
“…Extraversion has also been associated with higher levels of positive affect (Watson & Pennebaker, 1989). As such, extraversion can be expected to be associated with more positive relationships between parents and children.…”
Section: Extraversionmentioning
confidence: 99%
“…However, it should be noted that whereas emotional stability may tap into normal individual differences in depressive affect, it cannot be automatically equated with the pathological syndrome of depression. Finally, a low level of emotional stability has been linked to negative response tendencies in filling out questionnaires (Watson & Pennebaker, 1989). In parents, Belsky and Barends (2002) reviewed extensive evidence that depressive mood (associated with low emotional stability) is related to less competent caregiving (but see Prinzie et al, 2004).…”
Section: Emotional Stabilitymentioning
confidence: 99%